KOH and sea sand as green catalyst for biodiesel production - Sulaiman, Sarina; Mustafa Ahmed, Fatani (Lembaga Jurutera Malaysia, 2022)
Many developed countries have focused on generating energy from the earth’s resources, which is a key input for human wellbeing, social growth, economic progress and higher living standards. Biodiesel is a clean-burning, easy-tomake diesel made from fats or oils. Biodiesel can be made from either vegetable oil or animal fats, and it works in any diesel engine. This research aims to characterise the catalysts made of sea sand and potassium hydroxide and synthesise and optimise the use of green heterogeneous catalysts. The maximum biodiesel yield, at 76.7%, was obtained with a 1:1 KOH:sea sand ratio and with other fixed parameters such as reaction temperature (65°C), reaction duration (three hours), and methanol-to-oil ratio (15:1). This research has opened a new door for biodiesel production and has provided a safer, greener and more environment-friendly catalyst.